Tracing Truth : A Critical Study on the Authenticity of the Hadiths in Al-Bayan by Abdul Hamid Hakim (1893 M-1959 M) - Muhammad Hafizi; Luqmanul Hakim; Efrinaldi (JOURNAL OF QUR'AN AND HADITH STUDIES, 2025)
This research focuses on the problem of unclear hadith authentication and legal classification in Al-Bayan by Abdul Hamid Hakim, where many hadiths are cited without explanation of their sanad or legal status. Such absence of references raises questions about the methodological rigor and reliability of the hadiths used as istidlal (legal arguments). The study employs a qualitative method with a literature study approach, emphasizing takhrij al-hadith to trace the origins, authenticity, and legal implications of the hadiths. Through comparative analysis, the research identifies 165 hadiths, of which 129 are excluded because their rulings are clear and authenticated by al-Bukhari and Muslim, while 36 require further takhrij. From 103 hadiths analyzed in detail, 6 are hasan, 9 are da‘if, and the rest are sahih. The findings show that Abdul Hamid Hakim’s interpretive approach integrates the Qur’an, hadith, qiyas, and scholarly consensus, prioritizing moral and legal coherence over technical precision.